Perilaku Organisasi melalui Dakwah terhadap Perkembangan Manajemen Partai Keadilan Sejahtera Wilayah Gorontalo - Perdana, Dian Adi; Pakili, Mey Oktafiyanti (Institut Agama Islam Negeri Padangsidimpuan, 2020)
The behavior of an organization is largely determined by the behavior of each individual in the organization with the same aim to provide benefits to the surrounding environment. Cooperation and cohesiveness between individuals or groups in an organization cannot be separated from a leader figure because in organizations there must be various situational interactions that often lead to various pros and cons responses between parties for their respective goals. One of them happened in Partai Keadilan Sejahtera for Gorontalo Region which embraced members by implementing Islamic values in its activities, politics as a body, but da'wah was the main breath in organizational governance. This study discusses organizational behavior in political parties, namely Partai Keadilan Sejahtera for Gorontalo Region. This research is in a qualitative form that focuses on social and reality within the party which seeks to produce descriptive data from the speakers as well as observing their behavior by collecting data and analyzing it in order to present data and draw conclusions according to the problems found. The results of this study indicate that the Prosperous Justice Party applies da'wah in spreading its political influence. Da'wah carried out builds strong organizational behavior within the party, this has an impact on public trust or trust in the party. Beliefs based on Islam are implemented in various fields in 4 ways, namely Mihwar Tanzhimi, Mihwar Sya'bi, Mihwar Mu'assasi and Mihwar Dawlah as party political reforms